CONSTRUCTION OF STUDENTS' HISTORICAL LITERACY THROUGH ISLAMIC CULTURAL HISTORY LEARNING BASED ON DIGITAL ANIMATION VIDEOS - Novita Anggraeni; Devi Sulaeman; Mia Audina Musyadad; Dedeh Kurniasih; Asep Supriatna (JCI Publisher, 2026)
The development of digital technology in education is driving the transformation of history learning from a textual approach to a visual and interactive approach. In the context of Islamic education, learning Islamic Cultural History (ISHC) requires strategies that can build students' historical literacy reflectively and contextually. This study aims to describe and analyze the process of constructing students' historical literacy through digital animated video-based ISHC learning at Madrasah Aliyah Fathanul Burhan, Tempuran District. This research used a qualitative approach with a case study approach. Data were collected through participant observation, in-depth interviews, and documentation studies, then analyzed using an interactive model through the stages of reduction, presentation, and conclusion drawing. The results show that the use of digital animated video integrated into the learning design fosters chronological understanding, causal analysis skills, and active student engagement in reflective discussions. The teacher's role as a facilitator is a key factor in guiding students' interpretation of visual content, ensuring a systematic process of meaning construction. The implications of this research emphasize the importance of integrating digital pedagogy and dialogic facilitation in strengthening historical literacy in madrasas, as well as contributing to the development of SKI learning practices that are adaptive to the digital era.